Airway Clearance of the Term Newborn. Issue 6 (November 2018) - Adams, Ellise D.; O'Neal, Pamela V.; Hanson, Linda A.; Norris, Casey; Ayers, Angela; Harbin, Brandi
Abstract: Purpose: This descriptive, observational study explored the practice of airway clearance of the term newborn at birth. The American Academy of Pediatrics, the American Heart Association, and the European Resuscitation Council have established guidelines for suctioning the well newborn. Study Design and Methods: Airway clearance practices of nurses, obstetricians, and respiratory therapists at 10 cesarean births and 10 vaginal births were observed. Data were analyzed using descriptive statistics and through content analysis of narratives. Results: All newborns observed experienced at least one airway clearance event and multiple airway clearance passes. Indications for suctioning were not consistent with professional guidelines. Airway clearance procedures and practices were inconsistent. Two suction devices used: the blue bulb syringe and orogastric catheter. If a newborn was suctioned three times, the orogastric catheter was the predominate device used. Clinical Implications: There was a lack of adherence to established clinical guidelines for newborn airway clearance. Further study is needed to identify education of airway clearance guidelines. Specific protocols such as safe suctioning methods, correct device use, and observation of complications associated with airway management need to be developed to support a newborn's healthy transition at birth. Abstract : At birth, simple drying of the newborn, wiping away excess fluids from the newborn's mouth and nose, proper positioning of the airway and provision of a warm environment of a term newborn with spontaneous respirations, adequate crying, and good muscle tone are recommended practices. In this study, 40% of healthy newborns were suctioned at birth, although there were no indications. Why is it difficult to consistently apply practice guidelines in the clinical setting? The authors offer some insight on this common conundrum.